Enterprise Architecture Planning for the Coffee Shop Sector Using ADM at Big Coffee Signature - Christopher Winson Budiman; Richardus Eko Indrajit; Erick Dazki (Politeknik Pertanian Negeri Samarinda, 2025)
The coffee shop industry in Indonesia is experiencing rapid growth, along with the increasing demand for more innovative and efficient customer experiences. To maintain competitiveness and improve operational efficiency, coffee shop companies need to utilize technology in a structured manner. This study aims to design and develop an Enterprise Architecture (EA) model that can be applied to Big Coffee Signature in order to align business strategy with the technology used. In this study, the TOGAF and ArchiMate frameworks are used to design an enterprise architecture that is integrated with online ordering systems, digital payments, customer management, and raw material stock management. Through the implementation of EA, Big Coffee Signature can optimize the use of technology to improve operations and provide better customer experience. The application systems used, such as the Smart Ordering System, Multichannel Payment System, and Inventory Management System, are integrated to improve efficiency, transparency, and convenience for customers. This study also shows that by integrating third-party platforms such as GoFood and GrabFood, companies can expand their market reach and provide greater convenience for customers in placing orders. The results of the study show that the implementation of a structured EA can provide significant benefits in terms of operational efficiency, aligning technology with business needs, and improving customer service. The suggestions provided, such as further development of the customer loyalty system, utilization of AI for service personalization, and development of a cloud-based POS system, are expected to help Big Coffee Signature to increase the competitiveness and sustainability of their business.